Using African Indigenous Knowledge in Conceptualizing Peculiarities-Based Teacher Education Curricula for African Universities - Rufai, Saheed Ahmad; Adedeji, Luqman Lekan; Musa, Bello (Universitas Negeri Semarang, 2021)
The dominant nature of Western models of teacher education in African universities has become a subject of great concern. Research reveals that teacher education curriculum models in such universities are either a wholesale importation or partial duplication of some of the dominant models of teacher preparation especially the Teachers College, Columbia and University of Wisconsin, Madison models. Accordingly, such curricula are ostensibly non-African in nature. Consequently, there is a clamour for an African indigenous model with potential to produce African-based teachers for Africa and its Diaspora. This study which has Indigenous Knowledge as its theoretical basis attempts to formulate university-based Afrocentric teacher education curriculum. The study employs a multiplicity of methods comprising curriculum criticism, the historical method, the analytic method, and creative synthesis. Its significance lies in its potential to contribute to the promotion of the African identity through ideologically independent teachers for ultimate implementation of school curricula in Africa. Abstrak Dominasi pendidikan keguruan model Barat di universitas-universitas Afrika telah menjadi perhatian yang besar. Beberapa penelitian mengungkapkan bahwa model-model pengembangan kurikulum pendidikan keguruan sepenuhnya merupakan impor atau duplikasi dari model beberapa model dominan persiapan calon guru, terutama Teachers College, Columbia dan universitas Wisconsin, Madison. Dengan demikian, kurikulum yang dijalankan seolah-olah tidak kontekstual Afrika. Akibatnya, muncul tuntutan lahirnya model asli Afrika yang potensial menghasilkan guru-guru berbasis Afrika untuk Afrika dan diasporanya. Kajian ini menggunakan pengetahuan pribumi sebagai basis teoretik untuk mengembangkan kurikulum pendidikan keguruan berbasis universitas yang menempatkan nuansa dan konteks Afrika sebagai fokus utama. Kajian ini menggunakan beragam metode, antara lain kritik kurikulum, telaah sejarah, metode analitik, dan sintesis kreatif. Signifikansi kajian ini terlatak pada potensinya berkontribusi bagi promosi identitas Afrika melalui guru-guru yang secara ideologis independent untuk mengimplementasikan kurikulum sekolah-sekolah di Afrika secara optimal.